2015
DOI: 10.1542/peds.2014-2426
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination, Underlying Comorbidities, and Risk of Invasive Pneumococcal Disease

Abstract: OBJECTIVES: Children with underlying conditions remain at increased risk for invasive pneumococcal diseases (IPD). This study describes the epidemiology, serotype distribution, clinical presentations, and outcomes of IPD in children with and without comorbidity. RESULTS: Among 1052 IPD cases in Massachusetts children ,18 years old, 22.1% had at least 1 comorbidity. Immunocompromising conditions (32.7%) and chronic respiratory diseases (22.4%) were most common. Children with comorbidities were older at the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
1
41
1
Order By: Relevance
“…33 IPD risk is highest among children and adults with immunocompromised immune systems due to congenital or acquired immunodeficiency, immunosuppressive therapy, functional (e.g., sickle cell disease) or anatomic asplenia, chronic renal failure, or nephrotic syndrome. 7,32,34 In immunocompromised adults 18–64 years of age, the incidence of IPD is 100–400 cases per 100,000 30,33 compared with approximately 9 cases per 1000,000 in otherwise healthy adults in that age group. 31 Similarly, the risk of IPD in children under 5 years of age and 5 to 17 years of age with immunocompromising medical conditions is ~4-fold to ~40-fold higher compared with otherwise healthy children of the same age.…”
Section: Pneumococcal Disease In Children With Comorbid Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…33 IPD risk is highest among children and adults with immunocompromised immune systems due to congenital or acquired immunodeficiency, immunosuppressive therapy, functional (e.g., sickle cell disease) or anatomic asplenia, chronic renal failure, or nephrotic syndrome. 7,32,34 In immunocompromised adults 18–64 years of age, the incidence of IPD is 100–400 cases per 100,000 30,33 compared with approximately 9 cases per 1000,000 in otherwise healthy adults in that age group. 31 Similarly, the risk of IPD in children under 5 years of age and 5 to 17 years of age with immunocompromising medical conditions is ~4-fold to ~40-fold higher compared with otherwise healthy children of the same age.…”
Section: Pneumococcal Disease In Children With Comorbid Conditionsmentioning
confidence: 99%
“…Van Hoek et al reported increased case fatality rates, specifically in children with asplenia and chronic cardiac, pulmonary, and liver disease. 32,35 …”
Section: Pneumococcal Disease In Children With Comorbid Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study from Massachusetts showed no change in serotype 3 carriage rate after PCV13 introduction, although the numbers of serotype 3 cases overall admittedly were quite small (21).…”
Section: Discussionmentioning
confidence: 90%